PERSEPSI MAHASISWA FISIP UNDIP TERHADAP PANCASILA SEBAGAI IDEOLOGI NEGARA - jacobus william tengkar; Yuwanto . .; Turtiantoro . . (Journal of Politic and Government Studies, 2017)
Pancasila as the state ideology can’t be separated from the history of the nation. Starting from the old order until the reform era. In different era has their own interpretation about Pancasila. In this era of reform in accordance with the social reality that occurs Pancasila accepted only as a theory without understanding and appreciation. Students as educated people, especially college students who study in FISIP political theory and ideology become the generation that tried to understand Pancasila as an ideology.This research aimed to describe the perceptions of FISIP UNDIP students' about Pancasila as the state ideology. The type of this research is descriptive type. The primary data source is generated through a questionnaire with probability sampling techniques. For secondary data generated from documents, archives and internet. The techniques of data analysis in this research using descriptive analysis. The results showed that the students' knowledge about Pancasila are high. Emotional attachment still showing the students their faith or agree with Pancasila as an ideology but there are a few students who would doubt with the purity of Pancasila. The student assessment are regarding Pancasila that explained in reality the implementation of Pancasila as an ideology has not been fully implemented either individually or in a higher level that is in the government level. This is the evidenced by the many irregularities still occurred attitudes, behavior or actions that are inconsistent with Pancasila.From these results it can be concluded that the students did have a deep knowledge of the Pancasila but not with the appreciation of the Pancasila. Advice can be given the need for increased awareness of both the government and the public of the importance of Pancasila in its application.Keyword: Pancasila, Student, Ideology